Outcomes of endovascular embolization for Vein of Galen malformations: An individual participant data meta-analysis - Savage, Cody; Hale, Andrew T.; Parr, Matthew S.; Hedaya, Alexander; Saccomano, Benjamin W.; Tsemo, Georges Bouobda; Hafeez, Muhammad U.; Tanweer, Omar; Kan, Peter; Solomon, Laurent J.; Meila, Dan; Dirks, Peter B.; et al. (Frontiers in Pediatrics, 2022)
Introduction: Understanding outcomes after Vein of Galen malformation (VOGM) embolization has been limited by small sample size in reported series and predominantly single center studies. To address these limitations, we perform an individual-participant meta-analysis (IPMA) to identify risk factors associated with all-cause mortality and clinical outcome after VOGM endovascular embolization. Methods: We performed a systematic review and IPMA of VOGM endovascular outcomes according to PRISMA guidelines. Individual patient characteristics including demographic, intra/post-operative adverse events, treatment efficacy (partial or complete occlusion), and clinical outcome were collected. Mixed-effects logistic regression with random effects modeling and Bonferroni correction was used (p<0.003 threshold for statistical significance). The primary and secondary outcomes were all-cause mortality and poor clinical outcome (moderate/severe developmental delay or permanent disabling injury), respectively. Data are expressed as (mean  standard deviation (SD)) or (odds ratio (OR), 95% confidence interval (CI), I2, p-value) Results: Thirty-five studies totaling 307 participants quantifying outcomes after endovascular embolization for VOGM were included. Follow up time was 42 (+/- 57) months. Our analysis contained 42% neonates (< 1 month) at first embolization, 45% infants (1 month < 2 years), and 13% children (> 2 years). Complete occlusion was reported in 48% of participants. Overall all-cause mortality was 16%. Overall, good clinical outcome was achieved in 68% of participants. First embolization as a neonate (OR=6.93; 95% CI [1.99-24.08]; I2<0.01; p<0.001) and incomplete occlusion (OR=10.87; 95% CI [1.86-63.55]; I2<0.01; p<0.001) were associated with mortality. First embolization as a neonate (OR=3.24; 95% CI [1.47-7.15]; I2<0.01; p<0.001), incomplete occlusion (OR=5.26; 95% CI [2.06-13.43]; I2<0.01; p<0.001), and heart failure at presentation (OR=3.10; 95% CI [1.03-9.33]; I2<0.01; p=0.002) were associated with poor clinical outcomes. Sex, angioarchitecture of lesion, embolization approach (transvenous vs transarterial), and single or multistage embolization were not associated with mortality or clinical outcome. Conclusions: We identify incomplete VOGM embolization independently associated with mortality and poor clinical outcome. While this study provides the highest level of evidence for VOGM embolization to date, prospective multicenter studies are needed to understand the optimal treatment strategies, outcomes, and natural history after VOGM embolization.